Microwave interferometric technique for characterizing few mode fibers - Wang, Lixian; Jin, Cang; Messaddeq, Younes [UNESP]; Larochelle, Sophie (Institute of Electrical and Electronics Engineers (IEEE), 2014)
We propose and experimentally demonstrate a simple and accurate technique for measuring differential mode group delay (DMGD) in few mode fibers (FMF). A frequency-swept microwave signal is modulated on a filtered optical incoherent source. The microwave signals carried on different fiber modes experience different time delays and interfere with each other in the photodetector. Optical interference between propagating fiber modes is avoided by the use of an incoherent optical source. A mathematical model is established to analyze the interference pattern and extract the DMGD values. A 456-m two-mode fiber and a 981-m FMF, which supports four LP modes, are measured. The measurement covers the whole C-band and the results coincide well with those obtained by the time-of-flight method and the numerical simulations. A precision of ±0.002 ps/m is achieved.
Keywords: Optical fiber communication; Optical fiber testing; Optical fibers; Microwave photonics